FLORISTIC COMPOSITION AND DIVERSITY IN FOUR AMAZON RAINFOREST HABITATS FROM TAMBOPATA, MADRE DE DIOS, PERU - MARTÍNEZ-SOVERO, Gustavo (2023)
The Amazon rainforest is one of the most biodiverse and at the same time most threatened ecosystems in the biosphere. Its different habitats provide a unique floristic pattern. Therefore, we aimed to identify the floristic arboreal composition in an area of the Amazon rainforest and determine the local patterns of diversity in its different habitats. This study was conducted around the Tambopata Research Center, Madre de Dios, Peru. To achieve our goals, we established 20 (50 × 30 m) plots distributed equally in four habitats, these being: Mauritia Palm Swamp, Floodplain Forest, Successional Floodplain Forest, and Tierra Firme Forest. In each plot, we collected all individuals with a diameter at a breast height ≥ of 10 cm. Subsequently, the individuals were identified and classified by cluster and diversity analysis. We found 57 families, 173 genera, 300 species, and 1958 individuals. Fabaceae was the family with the highest number of genera (19) and species (36), while Arecaceae was the family with the highest number of individuals (603). Clustering analysis showed a high cophenetic correlation for habitats (0.94). The biodiversity analysis showed that the Floodplain Forest and the Tierra Firme Forest are the habitats with the highest floristic representation. This study evidences the richness of the Peruvian Amazon rainforest, at the same time that it observes the local patterns of each habitat.